HUBUNGAN KADAR TIMBAL DALAM DARAH DENGAN GANGGUAN KOGNITIF REMAJA JALANAN DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - , CLARA VALENCIA OKKYWULANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Lead pollution is an important issue in developing countries. It is caused by the disposal of motor combustion products or drinking water where lead-based plumbing pipes are still in use. Several studies have reported that lead has negative effect on health, such as the central nervous system, peripheral nerves, intelligence, cardiovascular, hematopoietic system, kidney, digestive and reproductive systems. Lead poisoning occurs in 49% of children under 6 years old in the United States. Exposure to lead in early life affects children's intelligence in which 278 African American children are affected with cognitive impairment. Aim: To determine the relationship between lead exposure from motor vehicle fumes on the streets and cognitive impairment in adolescents in DIY. Methods: This study was a cross-sectional study. The samples for this study were street adolescents, both male and female, aged 17-24 years. The total sample were 55 people. Data was taken from âYayasan Pinggir Jalan (Girlan) Nusantaraâ in D. I Yogykarta. Diagnosis of cognitive impairment was based on MMSE and CDT. Several other variables were also examined including : age, sex, duration of exposure, BMI, Blood Pressure and duration of education. Data were analyzed using univariate and bivariate analyzes to determine the relationship between the observed variables. Results: Of the 55 subjects, correlation test showed a statistically significant weak positive correlation between blood lead concentrations and MMSE scores (r = 0,2 - <0,4, p < 0,05). Correlation tests between blood lead concentration and CDT scores shows a a very weak positive correlation (r = 0,0 - <0,2) but is not stastically significant (p > 0,05). Conclusion: Lead levels on DIY street adolescents did not significantly affect MMSE and CDT scores. Another variable that influenced cognitive impairment is drug abuse, time spent on the streets, diastolic blood pressure, and duration of education.